Detecting the Growth Pattern(s) of the EU Border Regions: A Convergence Clubs Approach - Dimitris Kallioras; Panagiotis Artelaris; Lefteris Topaloglou; Maria Tsiapa (European Regional Science Association (ERSA), 2011)
The EU regions have been experiencing a period of unprecedented change. The ongoing (and parallel) processes of EU integration and enlargement have progressively transformed regional economies to integral parts of the emerging (European) socio-economic space, exposing them to the forces and the dynamics of a more competitive environment. Border regions, in particular, have been put in a state of flux since the re-(al)location of activities, opportunities and threats has changed over (the significance of) their role in the respective emerging (European) socio-economic map. Within the context of the aforementioned milieu, the paper aims at detecting and assessing growth determinants at the EU borderlands. This is an issue that has attracting increasing attention, especially after the creation of the Single European Market and the advent of the euro currency. However, the majority of border studies are enclaved in the "unitary case syndrome", without providing substantial added value on border theory. Thus, the present study, following an interdisciplinary approach, compiles a spatial econometrics growth model, incorporating a series of inherent and acquired growth determinants (initial conditions). These determinants are not only quantitative ("hard", "traditional") but also qualitative ("soft", "non-traditional"), accentuating the complexity of border issues. The study area covers 349 EU NUTS III border regions, as they are specified by ESPON. The findings of the paper are going to provide valuable insight for the understanding of the determinants of growth in EU border regions, having important implications for both theory and policy-making.
Keywords: 330